Isolation and reactivity of a chlorogermyliumylidene featuring two Ge – Cl units - Su, Yuanting (2020)
Deprotonation of 1‐mesityl‐4,5‐diphenyl‐2‐imidazole 1 with nBuLi, followed by salt metathesis reaction with GeCl2·dioxane complex, led to the formation of the chlorogermyliumylidene 2 bearing two Ge–Cl units, which has been isolated and fully characterized by standard spectroscopic and X‐ray diffraction analysis. Structural and NMR spectroscopic data as well as computational studies revealed that the positive charge mainly resides on the Ge atom between two nitrogen atoms. Reduction of 2 with an excess amount of lithium metal resulted in Ge–Ge bond formation concomitant with elimination of one of the Ge atoms of 2, to give rise to the digermylenedilithium compound 3 involving intramolecular coordination of the imines and the lone pairs to the Li atoms.